Delineation of the mechanisms of tendon gliding resistance within the carpal tunnel. (January 2017) - Filius, Anika; Thoreson, Andrew R.; Ozasa, Yasuhiro; An, Kai-Nan; Zhao, Chunfeng; Amadio, Peter C.
Abstract: Background: Forceful, high-velocity, and repetitive manual hand tasks contribute to the onset of carpal tunnel syndrome. This study aimed to isolate and identify mechanisms that contribute to tendon gliding resistance in the carpal tunnel. Methods: Eight human cadaver hands (four pairs) were used. Tendon gliding resistance (force, energy, and stiffness) was measured under different conditions: with intact and with divided subsynovial connective tissue, at 2 mm/s and 60 mm/s tendon excursion velocity, and with and without relaxation time before tendon excursion. Results: Subsynovial connective tissue stretching substantially contributed to increased gliding resistance force and energy during higher tendon excursion velocities, and subsynovial connective tissue stiffening was observed. Poroelastic properties of the tendon (and possibly the subsynovial connective tissue) also appear to be involved because relaxation time significantly increased gliding resistance force and energy ( P  < 0.01), and the difference in energy and force between high- and low-velocity tendon excursions increased with relaxation time ( P  = 0.01 and P  < 0.01). Lastly, without relaxation time, no difference in force and energy was observed ( P  = 0.06 and P  = 0.60), suggesting contact friction. Interpretation: These findings are consistent with the hypothesis that the mechanics of tendon motion within the carpal tunnel are affected by the integrity of the subsynovial connective tissue. While not tested here, in carpal tunnel syndrome this tissue is known to be the fibrotic, thickened, and less-fluid-permeable. An extrapolation of our findings suggests that these changes in the subsynovial connective tissue of carpal tunnel syndrome patients could increase contact friction and carpal tunnel pressure. Highlights: Subsynovial connective tissue stiffness is proportional to tendon gliding velocity. Subsynovial connective tissue stretch, poroelasticity and friction resist gliding. Carpal tunnel syndrome induced changes could further increase gliding resistance.